POLISH AND GERMAN INDUSTRY GUIDELINES IN THE SCOPE OF PREPARATION OF CERTIFIED TRANSLATIONS IN A CONTRASTIVE APPROACH ‒ PRACTICAL IMPLICATIONS FOR DRAWING CERTIFIED TRANSLATIONS OF POLISH AND GERMAN COURT JUDGMENTS - SEKUŁA, Justyna Katarzyna (Comparative Legilinguistics, 2019)
In the paper, the author undertakes a contrasting comparison of Polish industry guidelines for the preparation of certified translations contained in the Sworn translator's code with the following German guidelines: Richtlinien und Hinweise für die Anfertigung von Urkunden-übersetzungen and Empfehlungen für die Anfertigung bestätigter/beglaubigter Übersetzungen. Next, the results of the above comparison are referred to the certified translation of Polish and German court judgments.